Characterization of Oryza glaberrima derived genetic resources for stagnant flooding tolerance in interspecific rice pre-breeding populations - Semwal, Vimal Kumar; Bhadmus, Olatunde Azeez; Afeez, Shittu; Ramaiah, Venuprasad (Cambridge University Press (CUP), 2025)
Stagnant flooding (SF) is a unique and prolonged flooding condition characterized by standing water levels of 25–50 cm that persist for extended periods, sometimes throughout the entire crop duration. Most Sub1 introgressed rice varieties, while effective against flash flooding, remain susceptible to SF due to restricted shoot elongation. Tolerance to SF in the elite O. sativa genetic pool is very rare. This study represents the first comprehensive evaluation of interspecific pre-breeding populations developed from crosses between the tolerant African rice landrace GERVEX 2674 (Oryza glaberrima) and three sensitive O. sativa elite breeding lines. The populations were assessed under controlled and SF conditions across three seasons in Nigeria. GERVEX 2674 and its better-performing progenies exhibited moderate elongation and a higher number of tillers under SF, resulting in higher grain yield and plant survival under SF stress. Moderate elongation and high tillering ability were identified as key adaptive traits for maintaining higher productivity under SF. QTL analysis revealed 20 quantitative trait loci (QTLs) across nine chromosomes, with minor effects associated with key agronomic traits such as grain yield, survival percentage, days to 50% flowering, plant height, number of panicles and tillers. A key QTL identified for days to 50% flowering qdtf-12 explaining 10.5% of observed phenotypic variation. The best-performing lines from these interspecific pre-breeding populations showed strong promise for further utilization in breeding for improved SF tolerance in O. sativa.